2014
DOI: 10.1007/s40071-014-0069-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stocking density on the expression of glucose transporter protein 1 and other physiological factors in the Lake Victoria Nile tilapia, Oreochromis niloticus (L.)

Abstract: Fish farmers have a tendency of employing high stocking density (HSD) as a means of increasing productivity. However, HSD is a chronic stressor that is likely to lower profitability of fish farming if not implemented properly. HSD induces stress which in turn elevates sequentially the levels of plasma cortisol and glucose. The resultant glucose is distributed to various tissues by glucose transporter protein (GLUTs) to restore normalcy. GLUT 1, transmembrane protein found in erythrocytes, is responsible for im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…A C C E P T E D ACCEPTED MANUSCRIPT 14 L.), Nile tilapia, white sturgeon (Acipenser transmontanus), and rainbow trout (Oncorhynchus mykiss) [28][29][30][31][32]. Hormone concentrations could be very different between species.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…A C C E P T E D ACCEPTED MANUSCRIPT 14 L.), Nile tilapia, white sturgeon (Acipenser transmontanus), and rainbow trout (Oncorhynchus mykiss) [28][29][30][31][32]. Hormone concentrations could be very different between species.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…GLUT1 is responsible for the import and export of glucose into red blood cells. The effect of high density has been studied in Nile tilapia, Oreochromis niloticus, demonstrating an increase in glut1 expression, which can be used as a cellular stress biomarker in aquaculture [28]. The glut2 gene codes for the sodium-independent glucose transporter (GLUT2), and a significant increase in the number of glut2 mRNA copies in response to acute and chronic hypoxia has been demonstrated in liver of European seabass, Dicentrachus labrax, by Terova et al [29].…”
Section: Introductionmentioning
confidence: 99%
“…Commonly applied methods used in density studies include assessments of parameters involved in aquaculture production and nutritional status (mortality, body condition factor, food intake, food conversion rate, growth, and size variation), health condition (blood parameters, fin damage, gill condition, and spleen condition), as well as stress indicators (cortisol and glucose concentrations, and elevated oxygen consumption) (Ellis et al, 2002;North et al, 2006). Some endpoints, such as those involved in aquaculture production, nutritional status, health condition, and behavior can take longer to manifest and are thus predominantly applied to experiments lasting several weeks to months (Adams et al, 2007;Aketch et al, 2014;Alanärä and Brännäs, 1996;Boujard et al, 2002;Brown et al, 1992;de Oliveira et al, 2012). In contrast, other parameters involved in the immediate stress response, e.g., cortisol levels and gene expression, change rapidly and can be used to determine short term stress and stress recovery at time points ranging from several hours to a few days (Caipang et al, 2008a, b;Fast et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, high stocking densities can also result in an increase in stress levels due to intraspecific competition. Studies on different species and different experimental settings have indicated that both high and low stocking densities can cause severe stress in fish (Aketch et al, 2014;Alanärä and Brännäs, 1996;Brown et al, 1992;Costas et al, 2008;Jørgensen et al, 1993).…”
Section: Introductionmentioning
confidence: 99%